Analysis of Marketing Promotion and Positioning in a Distribution Company in Huancayo - Vega Elías, Cristhian Renzo; Rozas Zúñiga, Raquelyn; Flores-Dianderas, Katherine Roxana (LACCEI, 2024)
This study examines the relationship between marketing promotion and the positioning of a product distribution company in the Province of Huancayo, utilizing a non-experimental, cross-sectional, and correlational design. The research included a random sample of 183 customers selected from a population of 350, with inclusion criteria based on purchase frequency. Using expertvalidated surveys and reliability determined by Cronbach's Alpha, data were collected and analyzed using SPSS V.27 and Excel 2021. The results reveal that marketing promotion explains 41% of the positioning (R2 = 0.410), with high statistical significance (p-value = 0.000). The obtained regression equation is Log Y = 9.333 + 0.534 X1, indicating a positive relationship between the variables. Additionally, a moderate positive correlation (Spearman's Rho = 0.681, p = 0.000) was found between marketing promotion and positioning. The dimensions of marketing promotion (advertising, sales promotion, personal selling, public relations, and direct marketing) also showed significant correlations with positioning. The findings highlight the importance of well-implemented marketing promotion strategies to improve the company's positioning. Comparisons with previous studies reveal variations in the correlation magnitude, emphasizing the relevance of context and methodology employed.